Concepts and Categories of the General Theory of Law as a Legal, Methodological Science - Vladimir Valentinovich Kozhevnikov (Britain International for Academic Research (BIAR-Publisher), 2025)
The main problem in the article is to determine the significance of the conceptual and categorical apparatus of the general theory of law from the point of view of cognition of legal phenomena and processes. Its solution necessarily presupposes the solution of the following goals: 1) determination of the methodological role of legal concepts and categories; 2) substantiation of a) the relationship between legal concepts and legal categories; b) legal and doctrinal legal concepts. As a result of the research, the author came to the following conclusions: 1) concepts and categories are not an independent method of cognition or a part of it; 2) legal concepts and legal categories should be distinguished; 3) doctrinal concepts should be guided by legal (official) definitions.